Performance Analysis of Pharmacist and Influencing Factors in the Era of National Healt Insurance at Puskesmas - Satibi Satibi; Eliza Hanum Daulay; Gusti Ayu Oviani; Karina Erlianti; Achmad Fudholi; Dyah Ayu Puspandari (JURNAL MANAJEMEN DAN PELAYANAN FARMASI (Journal of Management and Pharmacy Practice))
Puskesmas is one of the first-rate health facilities that organizes National Health Insurance. Pharmacists, who are responsible for pharmacy at Puskesmas, must follow Pharmacy Service Standard at Health Center as stated in Minister of Health Regulation (MHR) no. 74 of 2016 to ensure patient safety, but in the implementation of pharmaceutical services in Puskesmas, it is not done according to the standard of performance in which pharmacists need to be done. The purpose of this study was to assess the suitability of performance with MHR No. 74 of 2016 and factors affecting performance. This research is an analytical descriptive research. Data were retrospectively retrieved through document search and completed with qualitative data through observation sheets. The study was conducted at Puskesmas Kota Yogyakarta, Brebes Regency, and Banjarmasin City. The variables studied were performance conformity with MHR No. 74 of 2016 and the factors that affect the performance of pharmacists in Puskesmas are the characteristics of pharmacists (age, gender, education level, duration of practice and income). The data were analyzed descriptively for the appraisal of pharmacist performance, and the factors influencing the pharmacist's performance were analyzed statistically with independent sample t-test and One Way ANOVA. The number of respondents in this study was 18 pharmacists. The result showed that the pharmacist performance at health center as a whole was 82,97% (high) with achievement of pharmacist performance on drug management aspect and clinical pharmacy in high category that is 76,94% for drug management, and 89% for clinical pharmacy. From the results of this study, it is showed that the influences are the age factor, education, duration of practice, and income on the performance of pharmacists.